Aplikasi Propas (Program Pengarsipan Surat) Pada Kantor Desa Cihambulu-Subang - Surtika Ayumida; Muhamad Tabrani; Fransisca Natalia; Kurnia Abdurrahman Hariri (LPPM STMIK Rosma, 2019)
The process of archiving mails at the Cihambulu Village office the writing is still conventional. there are some deficiency including the process of writing that is not neat, archiving still using the ledger. Therefore required a program that can solving the problem, so the problems that occur at this Cihambulu Village office can be resolved. The concept of designing this system refers to the activities of data processing incoming mail, data processing outgoing mail, disposition making, to the manufacture of incoming mail reports and outgoing mail. some stages in the development or design of this program are software requirements analysis, program design, program code generation, program testing. The making this program using JAVA programming language, MySQL as database and windows 7 as operating system. Research methods used in the design of this system is the method of interviewing, observation, and literature study. While the purpose of designing this system is to produce a mail archiving program so that it can assist employees in data processing incoming mail, data processing outgoing mail, disposition making, making reports incoming mails and outgoing mail.